Lecture capture and learner engagement strategies for industrial engineering distance education: results of a pilot program - Alicia Jenner; Michael Helwig; Arlette Ruffer (Production)
Abstract Paper aims This study examines issues affecting the efficacy of online course delivery using lecture capture technology. This form of instruction presents particular challenges when classes are comprised of a mix of students who participate synchronously and asynchronously. Originality The study examines a pilot program focused on improving the delivery of lecture capture courses, providing a framework for the implementation of similar programs at other institutions. Research method Program feedback as to the quality of the learning experience is obtained from the instructor, as well as from both synchronous and asynchronous online learners. Main findings The results provide insights into how students engage with the instructor and with one another in a lecture capture setting. Effective instructional practices are also identified. Implications for theory and practice The results provide important insights that can enhance the delivery of courses utilizing lecture capture technology across a range of educational contexts.